2018
DOI: 10.1039/c8an00895g
|View full text |Cite
|
Sign up to set email alerts
|

A novel “signal-on” photoelectrochemical sensor for ultrasensitive detection of alkaline phosphatase activity based on a TiO2/g-C3N4heterojunction

Abstract: The use of alkaline phosphatase (ALP) as a biomarker in some diseases including hepatitis, obstructive jaundice, osteoblastic bone cancer, and osteomalacia is important in clinical diagnosis. Furthermore, ALP activity detection is an essential hot topic in environmental monitoring, biomedical research, and other research fields. In this study, a novel "signal-on" photoelectrochemical (PEC) biosensor based on the ALP-catalyzed phosphorylation reaction was designed to sensitively detect ALP activity. In this des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The g-C 3 N 4 /metal-based materials (metal or metal oxide) can be synthesized by different methods for use as biosensors. The application of g-C 3 N 4 /metal oxide composites, including g-C 3 N 4 /ZnO, [103] g-C 3 N 4 /ZnO nanotubes, [104] ZnO nanodisks/g-C 3 N 4 quantum dots, [105] g-C 3 N 4 /TiO 2 nanotubes, [106] g-C 3 N 4 /TiO 2 NPs, [107] g-C 3 N 4 /TiO 2 nanosheets [108] and g-C 3 N 4 /WO 3 NPs, have been studied for the detection of biological substances by incorporaiton into PEC biosensors. [109] Xi et al reported hierarchically structured ZnO hybridized with g-C 3 N 4 as a new material for the nonenzymatic PEC sensing of hydrogen peroxide (H 2 O 2 ).…”
Section: Photoelectrochemistry-based G-c 3 N 4 Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The g-C 3 N 4 /metal-based materials (metal or metal oxide) can be synthesized by different methods for use as biosensors. The application of g-C 3 N 4 /metal oxide composites, including g-C 3 N 4 /ZnO, [103] g-C 3 N 4 /ZnO nanotubes, [104] ZnO nanodisks/g-C 3 N 4 quantum dots, [105] g-C 3 N 4 /TiO 2 nanotubes, [106] g-C 3 N 4 /TiO 2 NPs, [107] g-C 3 N 4 /TiO 2 nanosheets [108] and g-C 3 N 4 /WO 3 NPs, have been studied for the detection of biological substances by incorporaiton into PEC biosensors. [109] Xi et al reported hierarchically structured ZnO hybridized with g-C 3 N 4 as a new material for the nonenzymatic PEC sensing of hydrogen peroxide (H 2 O 2 ).…”
Section: Photoelectrochemistry-based G-c 3 N 4 Biosensorsmentioning
confidence: 99%
“…[106] Copyright 2016, Elsevier B.V.; (d, g) Reproduced with permission. [108] Copyright 2018, Royal Society of Chemistry; (e) Reproduced with permission. [103] Copyright 2015, Springer; (f) Reproduced with permission.…”
Section: Photoelectrochemistry-based G-c 3 N 4 Biosensorsmentioning
confidence: 99%
“…[16,45] Based on the observed photocurrent intensities, the functionalization of GO with NiTAPc reduced the rate of electron-hole recombination and resulted in steady photocurrent.…”
Section: Mechanism Of Sensor Operationmentioning
confidence: 99%
“…[6] Currently, RIF quantitation is performed using fluorescence spectroscopy, [7,8] ultraviolet-visible (UV-vis) spectroscopy, [9] high-performance liquid chromatography (HPLC)-ultraviolet spectroscopy, [10] and HPLCmass spectrometry, [11] which required much time and incurred high equipment and routine maintenance costs. [12][13][14][15] Photosensitive materials such as nanosemiconductors, Ru(II) complexes, organic compounds, composite photoelectric materials, and biological macromolecules [16][17][18][19] have been extensively used in the fields of bioanalysis and drug/contaminant quantitation. Photoelectrochemical (PEC) methods have particularly wide application prospects due to the above inherent advantages as well as their accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a series of photosensitive materials have been applied to the construction of PEC sensors, such as CdS, 19 MoS 2 –ZnO, 20 CdSeTe, 21 MgIn 2 S 4 , 22 g -C 3 N 4 , 23 TiO 2 , 24 polythiophene, 25 polyaniline, 26 etc. Among these photoactive materials, titanium dioxide (TiO 2 ) is the most popular photoactive material due to its excellent stability, innocuity and low price.…”
Section: Introductionmentioning
confidence: 99%